Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Sayur Di Desa Mekar Jaya Kecamatan Sungai Gelam Kabupaten Muara Jambi - Muhammad Imaduddin,; Hansen Rusliani,; Lidya Anggraeni, (Journal of Student Research, 2023)
This research was conducted with the aim of discussing the Analysis of the Factors Influencing the Income of Vegetable Farmers in Mekar Jaya Village, Sungai Kaca District, Muara Jambi Regency. The factors or variables used and examined for their effect on income are capital, land area, and price. This research is a quantitative method of multiple linear regression research and uses primary data obtained directly from respondents by filling out a questionnaire. The answers to the questionnaires were tested or analyzed using SPSS (Statistical Package For Social Science) 26 software. The results of the research that has been done show that capital partially affects the income of vegetable farmers. Land area partially does not affect the income of vegetable farmers. Prices partially do not affect the income of vegetable farmers. Then based on the results of the f test it was found that simultaneously capital, land area, and price did not affect the income of vegetable farmers in Mekar Jaya Village, Sungai Gelam District, Muara Jambi Regency.